A comprehensive model of information security factors for decision-makers. Issue 92 (May 2020) - Diesch, Rainer; Pfaff, Matthias; Krcmar, Helmut
Abstract: Decision-making in the context of organizational information security is highly dependent on various information. For information security managers, not only relevant information has to be clarified but also their interdependencies have to be taken into account. Thus, the purpose of this research is to develop a comprehensive model of relevant management success factors (MSF) for organizational information security. First, a literature survey with an open-axial-selective analysis of 136 articles was performed to identify factors influencing information security. These factors were categorized into 12 areas: physical security, vulnerability, infrastructure, awareness, access control, risk, resources, organizational factors, CIA, continuity, security management, compliance & policy. Second, an interview series with 19 experts from the industry was used to evaluate the relevance of these factors in practice and explore interdependencies between them. Third, a comprehensive model was developed. The model shows that there are key-security-indicators, which directly impact the security-status of an organization while other indicators are only indirectly connected. Based on these results, information security managers should be aware of direct and indirect MSFs to make appropriate decisions.